Computer interfacing - Dixey, Graham (Maplin series., 1994)
This book explains how computers interact with the world around them and therefore how to make them a useful tool. Topics covered include descriptions of all the components that make up a computer, principles of data exchange, interaction with peripherals, serial communication, input devices, recording methods, computer-controlled motors, and printers.